2014
DOI: 10.2355/isijinternational.54.148
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Intergranular M23C6 in Sensitized Type-347 Stainless Steel

Abstract: Formation of intergranular M23C6 carbides and thereafter Cr-depletion zones in commercially available type-347 stainless steels were observed by optical microscopy, conventional transmission electron microscopy and analytical transmission electron microscopy. At the early stage of sensitization, only NbC carbides were observed both intragranularly and intergranularly. At the later stage, formation of intergranular M23C6 carbides and intergranular corrosion were found. A model is proposed to describe the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…3(b). 16) In addition, a representative bright-field TEM image of these aligned precipitates showed that fine intragranular NbC precipitates were, in fact, associated with dislocations, as shown in Fig. 3(c).…”
Section: Tem Characterization Of Intragranular Nbcmentioning
confidence: 86%
See 2 more Smart Citations
“…3(b). 16) In addition, a representative bright-field TEM image of these aligned precipitates showed that fine intragranular NbC precipitates were, in fact, associated with dislocations, as shown in Fig. 3(c).…”
Section: Tem Characterization Of Intragranular Nbcmentioning
confidence: 86%
“…16) Moreover, striations across the sample were occasionally found, known as the curtain effect, probably caused by the uneven chemical composition of the sample, typically at grain boundaries.…”
Section: D Analysis By Sem Characterization and 3dmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical applications refer to industries as oil extraction, re neries, thermo-electric and nuclear power plants due to its high corrosion resistance at high temperature 2) . The principal characteristics of this alloy are the combination of good mechanical property and corrosion resistance in comparison to conventional ASS due to the presence of Nb which reduces the sensitization phenomenon and increases creep resistance as a result of the formation of NbC 3) . Thermodynamically, the formation of niobium carbides are more favored and takes place in a broader range of temperatures 4) as compared to chromium carbides (450-850 C) 5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation of NbC occurs in grain boundaries, non-coherent twin boundaries, dislocations and stacking faults 5,7,8) . A requisite for nucleation and growth of niobium carbides is met when there is at least a Nb:C mass ratio of 10:1 3) . In this alloy, the highest af nity of C for Nb than Cr enhances the resistance to intergranular corrosion (IGC) by reducing the susceptibility to localized attack in virtue of the minimization of chromium depleted zones 9) .…”
Section: Introductionmentioning
confidence: 99%